INFLUENCE OF MUSCLE SLEEVE STRENGTH, TOGOK FORMATION, EYE COORDINATION AND SELF-CONFIDENCE IN SERVICE SKILLSTENNIS COURT - Muhammad Ali; Mulyana Mulyana; Firmansyah Firmansyah (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
This study aims to analysis the direct and indirect effect of hand strength, trunk flexibility, hand eye coordination and self confidence to the tennis service skills. The research was conducted on tennis athletes in Jambi City at outdoor tennis court Jambi University Telanai Pura Jambi City Jambi Province.The research method used in this research is the type of quantitative research with correlation study approach. Analytical technique using path analysis.The results of this study indicate that: 1) Hand strength has a direct effect to the self confidence of tennis athletes of Jambi in the amount of 23.52%; 2) The trunk flexibility has a direct effect to the self confidence of tennis athletes of Jambi in the amount of 8.24%; 3) Hand eye coordination has no direct effect to the self confidence of tennis athletes of Jambi with magnitude of influence only 2.86%; 4) Hand strength has a direct influence on service skills of tennis athletes of Jambi in the amount of 10.56%; 5) The trunk flexibility has a direct influence on service skills of tennis athletes of Jambi in the amount of 14.82%; 6) Hand eye coordination does not have a direct impact on service skills of tennis athletes of Jambi with magnitude of influence only 0.04%; 7) Confidence has a direct influence on service skills of tennis athletes of Jambi in the amount of 7.95%; 8) Hand strength has an indirect effect on the service skills of tennis athletes of Jambi through self confidence in the amount of 4.45%; 9) The trunk flexibility has an indirect influence on service skills of tennis athletes of Jambi through self-confidence in the amount of 3.12%; and 10) Hand eye coordination does not have an indirect effect on the service skills of Jambi's tennis athletes through self confidence with magnitude of influence only 0.09%. Keywords: Service skills, hand strength, trunk flexibility, hand eye coordination, and self confidence